Shocking Racial Attitudes: Black G.I.s in Europe - David Schindler; Mark Westcott (Center for Economic Studies and ifo Institute (CESifo), 2017)
Can attitudes towards minorities, an important cultural trait, be changed? We show that the presence of African American soldiers in the UK during World War II reduced anti-minority prejudice, a result of the positive interactions which took place between soldiers and the local population. The change has been persistent: in locations in which more African American soldiers were posted there are fewer members of the UK's leading far-right party, less implicit bias against blacks and fewer individuals professing racial prejudice, all measured around 2010. We show that persistence has been higher in rural areas and areas with less subsequent in-migration.
Keywords: J17; N00; Z10; 330